POLITIK UANG DALAM PEMILUKADA : FAKTOR KRIMINOGENIK KEJAHATAN KORUPSI - abdul munir; Setyo Prihatin, Panca; Khotami (Education and Talent Development Center of Indonesia, 2022)
Money politics is defined as the process of buying and selling people's votes by giving a reward. Getting used to the phenomenon of money politics in the community in every election celebration is suspected to be due to a lack of public awareness of the impact of the process which will eventually lead to the birth of corruption crimes at the power elite level. The purpose of this Community Service is to restore public awareness as part of efforts to prevent the latent dangers of corruption in the future. This Community Service was carried out in Darussalam Village, Sinaboi District, Rokan Hilir Regency, Riau Province. Participants in the activity were limited to groups of community leaders, related village officials and the local Babinkamtibmas and Babainsa. Through this activity, it is hoped that every participant who has received socialization materials can do important things according to their respective capacities in order to prevent money politics in the community.